Performa Jurusan Teknik Elektro ditinjau dari Prestasi Dosen dan Mahasiswa - Yuni Rahmawati; Tri Atmadji; Suwasono Suwasono; Dila Umnia Soraya (Fakultas Teknik Universitas Negeri Malang, 2019)
This research aimed to describe the performance of the Electrical Engineering Department viewed from the lecturers and students' achievements. The lecturers' achievements were seen from the Three Pillars of Higher Education, whereas the students' accomplishments were observed from academic achievement, organizational, competition, and graduates quality. The subject of this research were all lecturers and students from six study programs in Electrical Engineering Department. This research used quantitative descriptive analysis. The results showed that the performance of Electrical Engineering Department seen from lecturers' achievements containing the Three Pillars of Higher Education comprises of education, research, and community service was